Cost-effectiveness of Bezlotoxumab Compared With Placebo for the Prevention of Recurrent Clostridium difficile Infection. (2nd November 2017) - Prabhu, Vimalanand S; Dubberke, Erik R; Dorr, Mary Beth; Elbasha, Elamin; Cossrow, Nicole; Jiang, Yiling; Marcella, Stephen
Abstract : A natural history model of a range of adult patients with Clostridium difficile infection (CDI) treated with standard-of-care antibiotics showed that bezlotoxumab was cost-effective compared to placebo for the prevention of recurrent CDI episodes. Abstract: Background: Clostridium difficile infection (CDI) is the most commonly recognized cause of recurrent diarrhea. Bezlotoxumab, administered concurrently with antibiotics directed against C. difficile (standard of care [SoC]), has been shown to reduce the recurrence of CDI, compared with SoC alone. This study aimed to assess the cost-effectiveness of bezlotoxumab administered concurrently with SoC, compared with SoC alone, in subgroups of patients at risk of recurrence of CDI. Methods: A computer-based Markov health state transition model was designed to track the natural history of patients infected with CDI. A cohort of patients entered the model with either a mild/moderate or severe CDI episode, and were treated with SoC antibiotics together with either bezlotoxumab or placebo. The cohort was followed over a lifetime horizon, and costs and utilities for the various health states were used to estimate incremental cost-effectiveness ratios (ICERs). Both deterministic and probabilistic sensitivity analyses were used to test the robustness of the results. Results: The cost-effectiveness model showed that, compared with placebo, bezlotoxumab was associated with 0.12 quality-adjusted life-years (QALYs) gained and was cost-effective in preventing CDI recurrences in the entire trial population, with an ICER of 19824/QALY gained. Compared with placebo, bezlotoxumab was also cost-effective in the subgroups of patients aged ≥65 years (ICER of 15298/QALY), immunocompromised patients (ICER of 12597/QALY), and patients with severe CDI (ICER of 21430/QALY). Conclusions: Model-based results demonstrated that bezlotoxumab was cost-effective in the prevention of recurrent CDI compared with placebo, among patients receiving SoC antibiotics for treatment of CDI.